How I Grow: Months Nine and Ten - Millie Ferrer; Anne M. Fugate (EDIS)
Months nine and ten mark an exciting spurt in your baby’s development. This “growth spurt” is fueled by her great curiosity. She wants to look at, feel, taste, and move everything. Because she wants to explore, she is learning how to get around. Your baby’s curiosity is necessary and wonderful. It is the foundation of a lifetime of learning. As much as ever, your baby needs you to encourage and nurture her curiosity. At this stage of her development, that means letting her have as much freedom to explore her environment as possible. To keep her safe and prevent her from being spoiled, you will need to set and enforce limits. By giving your baby freedom to explore and providing safe, reasonable limits, you will help her develop physically, socially, emotionally, and intellectually. This document is FCS2221, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, IFAS, Gainesville, FL 32611. First published: August 2003.